Ab initio calculations of the geometry and polarizabilities of bisphenyls having aliphatic substituents - Sulatha, M. S.; Natarajan, U. (International Journal of Quantum Chemistry, 2011)
Ab initio geometry optimization and polarizability calculations of a series of bisphenyls, which are the model compounds of chemically different polycarbonates using HF/6-31G and 6-31G** basis sets are presented. Calculated absolute value of the conformationally averaged optical anisotropy (<gamma(2)>) of diphenyl propane, a model analog of bisphenol A polycarbonate, is higher than the corresponding experimental value in the dilute solution phase. The calculations have reproduced the relative trend in the optical anisotropy for the different bisphenyl model compounds in a manner similar to those using semiclassical approach, by incorporation of the condensed phase polarizabilities and quantum chemically calculated geometry structure into the valence optical scheme. Individual contributions to the gas phase polarizability and optical anisotropy of the model compounds for various dihedral conformers, because of the presence of different aliphatic chemical groups, are correctly predicted by the calculations here. (C) 2010 Wiley Periodicals, Inc. Int J Quantum Chem 111: 1092-1100, 2011</gamma(2)>
Keywords: ab initio; bisphenyl; optical anisotropy; polarizability; Polycarbonate; structure